2020
DOI: 10.1038/s41598-020-59008-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Transcriptional Dynamics Between T-cells and Macrophages as Determined by a Three-State Mathematical Model

Abstract: HIV-1 viral transcription persists in patients despite antiretroviral treatment, potentially due to intermittent HIV-1 LTR activation. While several mathematical models have been explored in the context of LTR-protein interactions, in this work for the first time HIV-1 LTR model featuring repressed, intermediate, and activated LTR states is integrated with generation of long (env) and short (TAR) RNAs and proteins (Tat, Pr55, and p24) in T-cells and macrophages using both cell lines and infected primary cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…Due to the variations in the frequency of sexual practices in MSM [14], we conducted sensitivity analyses to assess the impact of varying the selected parameters (frequency of solo masturbation and mutual masturbation and proportion of saliva used for solo masturbation and mutual masturbation) on the uncertainty of model calibration and the incidence. Sensitivity analysis was performed using the Latin hypercube sampling method, and we confirmed the model's robustness concerning small parameter perturbations [24]. (Further details are provided in the supplementary Table S3).…”
Section: Methodsmentioning
confidence: 70%
“…Due to the variations in the frequency of sexual practices in MSM [14], we conducted sensitivity analyses to assess the impact of varying the selected parameters (frequency of solo masturbation and mutual masturbation and proportion of saliva used for solo masturbation and mutual masturbation) on the uncertainty of model calibration and the incidence. Sensitivity analysis was performed using the Latin hypercube sampling method, and we confirmed the model's robustness concerning small parameter perturbations [24]. (Further details are provided in the supplementary Table S3).…”
Section: Methodsmentioning
confidence: 70%
“…Previously, we showed that HIV-1 gene expression is characterized by stochastic variability which results in paused polymerase and intermittent transition from latent to active state that allows the synthesis of mostly short non-coding RNAs (i.e., TAR) [ 19 , 20 , 36 , 37 , 38 ]. Paused RNA polymerase II allows synthesis of at least four distinct species of RNA that form a specific set of secondary structures [ 16 , 28 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, high levels of NF-κB and P300 were observed in the nuclei of latent cells cocultured with exosomal vesicles [171]. These vesicles can be targeted with antibodies, antibiotics, drugs, transcription inhibitors, and ARTs to alter the ratio/amount of their individual components and subsequently alter their roles in HIV latency upkeep/reversion [173,174]. For example, ARTs (Indinacir and Emitricitabine), antibiotics (oxytetracycline, tetracycline, methacycline, and demeclocycline), and even interferon treatments showed effects on the proteins in-volved in the endosomal sorting complex required for transport (ESCRT) pathway and caused changes in TAR RNA levels and other contents of these exosomal vesicles [173].…”
Section: Transcriptional and Genetic Factors In Hiv Latencymentioning
confidence: 99%
“…For example, ARTs (Indinacir and Emitricitabine), antibiotics (oxytetracycline, tetracycline, methacycline, and demeclocycline), and even interferon treatments showed effects on the proteins in-volved in the endosomal sorting complex required for transport (ESCRT) pathway and caused changes in TAR RNA levels and other contents of these exosomal vesicles [173]. In addition, incorporation of a transcriptional inhibitor F07#13 in a mathematical model in various cell types displayed potential to induce changes in HIV latency and LTR dynamics and were different among the cell types used [174]. In a study that used a library of FDAapproved drugs, HIV-1 proviral transcription was activated with febuxostat, eltrombopag, and resveratrol, while mycophenolate inhibited HIV-1 proviral transcription, and these transcriptional modulators exhibited different effects in different cell types (lymphoid versus myeloid lineage) [175].…”
Section: Transcriptional and Genetic Factors In Hiv Latencymentioning
confidence: 99%